Analisis Praktik Audit Big Data Environtment di Indonesia - Rahmadhani, Silvia; Lim, Jimmy; Santikawati, Santikawati (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
This study aims to determine auditing in the Big Data of Environment which is combined with the status of research on big data auditing at home and abroad and based on the characteristics of the big data environment. The method used in this study is descriptive qualitative with a literature review. The results of this study are as the newest product of innovation and integration of a new generation of information technology, big data has had a significant impact on various fields. This research proposes logical workflow and technical methods of data-driven auditing and proposes suggestions on building big data audit platforms, information sharing, talent training, and data security, providing ideas for research and practice of big data auditing modes.